2007
DOI: 10.1086/513197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prior Antiplatelet Therapy on Risk of Embolism in Infective Endocarditis

Abstract: The risk of symptomatic emboli associated with IE was reduced in patients who received continuous daily antiplatelet therapy before onset of IE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 45 publications
(48 reference statements)
5
72
0
5
Order By: Relevance
“…Prospective and retrospective studies of adult patients report conflicting results on the role of aspirin therapy in preventing cerebral embolic events. These may reflect differences in dosing and duration of therapy [14,15]. Two patients in our series were placed on aspirin therapy at doses of 3-5 mg/kg/day with no adverse cerebral events.…”
Section: Discussionmentioning
confidence: 92%
“…Prospective and retrospective studies of adult patients report conflicting results on the role of aspirin therapy in preventing cerebral embolic events. These may reflect differences in dosing and duration of therapy [14,15]. Two patients in our series were placed on aspirin therapy at doses of 3-5 mg/kg/day with no adverse cerebral events.…”
Section: Discussionmentioning
confidence: 92%
“…None of our patients had prosthetic heart valves. We also excluded those being treated with platelet-inhibitors since a previous study reported reduced risk of symptomatic emboli associated with IE in patients who received continuous daily antiplatelet therapy before onset of IE [33].…”
Section: Discussionmentioning
confidence: 99%
“…No benefi ts from anticoagulation were demonstrated once antimicrobial therapy was begun. Similarly, Anavekar et al 14 showed that embolic events occurred signifi cantly less often in those who were currently on continuous daily antiplatelet therapy, suggesting that receiving antiplatelet agents at baseline protects against cardioembolic events in patients who develop infective endocarditis. However, the only randomized trial examining the initiation of antiplatelet therapy in patients diagnosed with infectious endocarditis receiving antibiotic treatment showed that adding aspirin did not reduce the risk of embolic events and was associated with a trend toward increased risk of bleeding.…”
Section: ■ Available Evidence Is Scarce and Mixedmentioning
confidence: 96%